The Tradition of Ajege Kobhur: Local Wisdom of the Glingseran Village Community Bondowoso Regency - Rieski Triyanto, Jefri; Prasetyo , Guruh; Putri Nirmala Puji , Rully; Arif Budiman Nasution, Ahmad; Soepeno, Bambang (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
The Ajege Khobur tradition is part of the belief system and social practices that are closely related to the values of spirituality, cooperation, and respect for ancestors that have taken root in Glingseran Bondowoso village. This research seeks to reveal how the background of the Ajege Khobur tradition in Glingseran Village still survives as a form of cultural respect and preservation of the community's collective memory amid modernization. In addition, this study also explores the process, values, and influence of the Ajege Khobur tradition on the formation of local identity and its role in strengthening social solidarity among the community. This study aims to examine the Ajege Khobur tradition as part of local wisdom that is still practiced by the community in Glingseran Bondowoso village. The method used is descriptive qualitative. The results showed that the Ajege Khobur tradition is still maintained to this day because this practice not only has historical value but also has the value of local wisdom and cultural identity for the supporting community